The material cradle of the profile - Carramo, Renata; Lemos Martins, Jaqueline (Folios, revista de la Facultad de Comunicaciones y Filología, 2022)
This paper addresses The New Yorker magazine as the material cradle of the journalistic profile since its release, in 1925, in the context of literary journalism, its spiritual cradle. The bibliographic study deals with the favorable conditions for the exercise of the magazine’s extensive and quality journalistic narrative, thus listening to the voice and dealing with the output of its current director, David Remnick, and concluding with the empirical analysis of Joe Gould’s Secret (Joseph Mitchell) and Hiroshima (John Hersey) as examples of the use of journalistic profiling as an essential part of the narratives.